Bone health and fracture risk in diabetes: A multicenter study - Gul, Ozen Oz; Canturk, Zeynep; Ozturk, Sadettin; Ozdemir, Nilufer; Candemir, Dilek Kilinc; Ozbas, Burak; Ozkaya, Guven (Springer London Ltd, 2026)
We assessed bone health in over 2500 adults with diabetes across T & uuml;rkiye. T1DM patients had lower BMD, while T2DM patients showed higher fracture risk despite higher BMD. Several modifiable factors were linked to osteoporosis. These findings support personalized bone assessments in diabetic populations.BackgroundDiabetes mellitus (DM) is a recognized risk factor for bone fragility. While type 1 DM (T1DM) is typically associated with low bone mineral density (BMD), type 2 DM (T2DM) often presents with higher BMD despite increased fracture risk. Large-scale comparative studies remain limited.ObjectiveTo evaluate bone health, including osteopenia, osteoporosis, and fracture risk, in adults with T1DM and T2DM.MethodsThis multicenter, cross-sectional study included 2562 patients (224 with T1DM, 2338 with T2DM) from 27 centers across T & uuml;rkiye. BMD was assessed using dual-energy X-ray absorptiometry (DXA) and fracture risk was estimated via the Turkish-adapted FRAX (R) algorithm in patients aged >= 40 years. Multinomial logistic regression was used to identify independent predictors of low BMD.ResultsOsteoporosis prevalence was 5.5% in T1DM and 9.6% in T2DM (femoral neck T-score). Adjusted BMD was significantly lower in T1DM at all skeletal sites, while FRAX-based fracture risk and fall-related fractures were higher in T2DM. Independent predictors of osteoporosis included older age, female sex, lower BMI, reduced calcium levels, corticosteroid use, albuminuria, hypertension, and less frequent sodium-glucose cotransporter-2 (SGLT2) inhibitor use. T1DM was independently associated with osteopenia but not osteoporosis.ConclusionThis multicenter study demonstrates distinct patterns of BMD and fracture risk across diabetes subtypes and supports individualized bone health assessment in routine diabetes care.
Keywords: Diabetes mellitus; Type 1 diabetes; Type 2 diabetes; Osteoporosis; Bone mineral density; FRAX